Axiological aspects of teaching Spanish in the Soviet Union - E. V. Novoselova; N. I. Chernova; N. V. Katakhova (Российский технологический журнал)
Objectives. The paper analyzes core axiological aspects of Spanish teaching in higher educational institutions of the Soviet Union from the 1930s to the early 1980s based on various sources including textbooks, tutorials, etc. Methods. The study is based on textual-analytic, historical-comparative, and structural methods.Results. Scientific-pedagogical and sociological aspects of the subject are distinguished. The former are limited to the internal developmental logic of Spanish studies, while the latter refers to external circumstances, including ideological factors. The literature review shows that Spanish teaching in the USSR progressed topically from simple manuals aimed at consolidating linguistic basics to a more rigorous pedagogical development of Spanish language studies (grammar, phonetics, vocabulary, etc.) The authors identify two significant periods in the development of Soviet Spanish studies, with the first phase extending from the 1930s to the early 1960s, and the second—from the 1960s to the early 1980s.Conclusions. The analysis showed that the formation and development of each period is associated with such events as the Spanish Civil War and the victory of the Cuban Revolution, which are not directly related to Spanish teaching. The first event coincided with the beginning of systematic Spanish teaching at the USSR universities, while the second redirected this process from Castilian to Latin American Spanish. However, the analysis of textbook and tutorial materials convincingly demonstrates that this process of redirection, which mainly concerns the selection of textual materials, remains incomplete. This supports a conclusion concerning the limited impact of ideology on the internal logic of the Spanish studies development in the USSR.